2020
DOI: 10.1007/s00107-020-01620-y
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting bankruptcy in the wood industry

Abstract: The assessment of a company’s financial condition is an effective tool, which supports the management system. Nowadays a number of models are available, most often multi-branch ones, which are able to predict the financial situation of an enterprise. Models solely intended for just one line of business are a rarity. As far as the wood sector is concerned, no homogenous model suited to the sector has been created. The article aims to present the final stage of research dealing with predicting bankruptcy in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Subsequently, Barniv and Agarwal (2002) considered that profitability, working capital position, financial risk, and liquidity are the four key dimensions in establishing the financial profile of a company. Gavurova et al (2017) evaluated four models of bankruptcy prediction in the Slovak economy, in order to identify the optimal prediction model for it, finding that the use of the IN05 index (Neumaier & Neumaierová, 2004) is superior to the Ohlson (1980) and Altman models. Also, Boďa and Úradníček (2016), verified the applicability of the equation from the Altman model to the economic conditions in Slovakia, finding that the original wording and especially the revised one can be applied.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, Barniv and Agarwal (2002) considered that profitability, working capital position, financial risk, and liquidity are the four key dimensions in establishing the financial profile of a company. Gavurova et al (2017) evaluated four models of bankruptcy prediction in the Slovak economy, in order to identify the optimal prediction model for it, finding that the use of the IN05 index (Neumaier & Neumaierová, 2004) is superior to the Ohlson (1980) and Altman models. Also, Boďa and Úradníček (2016), verified the applicability of the equation from the Altman model to the economic conditions in Slovakia, finding that the original wording and especially the revised one can be applied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sulub (2014) found that Altman's Z model for predicting the financial crisis is correct for multinational companies that failed at a predictive power of 70%, and for those that failed with a predictive power of 55%. Giacosa et al (2016) used the models: discriminatory analysis (Altman, 1983), Taffler (1983) and logit analysis (Ohlson, 1980) for companies in Italy, finding that re-estimated models have a higher efficiency in making bankruptcy prediction compared to original models. Peyman et al (2011) applied the Springate and Zmijewski models for bankruptcy forecasting, applying non-parametric binomial methods for data analysis, finding that there is a significant difference between them in terms of forecasting accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Platt and Platt (2002) conducted research for the US car industry. Interestingly also is that many authors took effort to estimate the bankruptcy model for less popular sectors like the wood industry (Noga and Adamowicz 2021), telecommunication sector (Busu 2015), and agricultural entities (Valaskova et al 2020). Štefko et al (2021) used graphic methods and the DEA for predicting bankruptcy risk based on Slovak heat-management companies.…”
Section: Introductionmentioning
confidence: 99%